1984
DOI: 10.1128/jcm.20.5.985-987.1984
|View full text |Cite
|
Sign up to set email alerts
|

Plesiomonas shigelloides in acute cholecystitis: a case report

Abstract: Plesiomonas shigelloides was isolated as the sole pathogen from gallbladder bile and wall in a 58-year-old woman with acute cholecystitis. The patient developed an unusual postoperative complication characterized by culture-negative discharge from the wound in combination with extensive abdominal cellulitis and afebriity. Agglutinating antibodies to P. shigelloides were demonstrated in the serum of the patient by the microscopic Widal agglutination test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 11 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Accurate estimates of the incidence of Plesiomonas-related gastroenteritis and extraintestinal infections both globally and at the level of individual countries remain unknown [1,2,[4][5][6][7]10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Retrospective reviews of infections due to P. shigelloides in China and Hong Kong have been published [38], and cases of P. shigelloides co-infection with viral and bacterial diarrheal pathogens are common in the literature [39].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate estimates of the incidence of Plesiomonas-related gastroenteritis and extraintestinal infections both globally and at the level of individual countries remain unknown [1,2,[4][5][6][7]10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Retrospective reviews of infections due to P. shigelloides in China and Hong Kong have been published [38], and cases of P. shigelloides co-infection with viral and bacterial diarrheal pathogens are common in the literature [39].…”
Section: Introductionmentioning
confidence: 99%
“…2000). This species has also been implicated in an increasing number of extraintestinal infections, such as septicaemia, meningitis, cholecystitis, osteomyelytis and pseudoappendicitis (Claesson et al. 1984; Fischer et al.…”
Section: Introductionmentioning
confidence: 99%
“…This was further supported by various extraintestinal infections associated with Plesiomonas , including peritonitis (Alcañiz et al, 1995; Patel et al, 2016), cellulitis (Gopal and Burns, 1991; Jönsson et al, 1998), wound and foot infections (McCracken and Barkley, 1972; Herve et al, 2007; Pence, 2016), endophthalmitis (Butt et al, 1997; Mahrshmann and Lyons, 1998), and keratitis (Butt et al, 1997; Klatte et al, 2012). In addition, pneumonia (Schneider et al, 2009), migratory polyarthritis (Gupta, 1995), cholecystitis (Claesson et al, 1984; Kennedy et al, 1990), pyosalpinx (Roth et al, 2002), pseudo-appendicitis (Fischer et al, 1988), cholangitis and pancreatitis (Kennedy et al, 1990) are examples of infections that required invasive factor that have been reported caused by Plesiomonas . Further, Binns et al (1984) showed that 31.3% of examined strains are invasive toward HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…These include gastroenteritis and various forms of diarrhea (Tsukamoto et al, 1978; Wong et al, 2000; Chakour et al, 2002; Klontz et al, 2012; Pfeiffer et al, 2012; Novoa-Farías et al, 2016). Of major concern are extraintestinal infections of the central nervous system, such as neonatal meningoencephalitis, meningitis, sepsis, and septic shock (Claesson et al, 1984; Kalotychou et al, 2002; Auxiliadora-Martins et al, 2010; Ozdemir et al, 2010; Xia et al, 2015; Bowman et al, 2016). Other infections include peritonitis (Alcañiz et al, 1995), cellulitis (Gopal and Burns, 1991; Jönsson et al, 1998), wound and foot infections (McCracken and Barkley, 1972; Herve et al, 2007; Pence, 2016), endophthalmitis (Butt et al, 1997; Mahrshmann and Lyons, 1998), and keratitis (Butt et al, 1997; Klatte et al, 2012).…”
Section: Introductionmentioning
confidence: 99%